Fragmented QRS on far‐field intracardiac electrograms as a predictor of arrhythmic events. Issue 5 (21st August 2021) - Osaka, Yuki; Ono, Yuichi; Goto, Kentaro; Yabe, Kento; Tanaka, Akifumi; Miyazaki, Toru; Suzuki, Asami; Kurihara, Ken; Goya, Masahiko; Otomo, Kenichiro; Sasano, Tetsuo
Abstract: Background: Studies suggest that fragmented QRS (fQRS) can predict arrhythmic events in various cardiac diseases. However, the association between fQRS recordings on intracardiac electrogram (EGM) and ventricular arrhythmic events remains unknown. Methods: We enrolled 51 patients (age, 62 ± 12 years; 40 men) with an implantable cardioverter‐defibrillator (ICD) and structural heart disease and evaluated surface electrocardiogram (ECG) and EGM measurement of fQRS and the association between fQRS and arrhythmic events. Results: fQRS was detected on surface ECG and ICD‐EGM in 12 (23.5%) and 15 (29.4%) patients, respectively. fQRS was detected more frequently on ICD‐EGM in patients with fQRS on surface ECG than in patients without fQRS (7/12 [58.3%] vs 8/39 patients [20.5%], P  = .01). Appropriate ICD therapies were documented in 16 patients. Among these patients, fQRS was detected more frequently on surface ECG and ICD‐EGM in patients with appropriate ICD therapies (8/16, 50.0%; P  = .001 and 11/16, 68.9%; P  < .001). Nonsustained ventricular tachycardia was significantly more frequent in patients with appropriate ICD therapies (15/16, 93.8%; P  = .04). Multiple logistic regression analysis showed that fQRS on ICD‐EGM was a predictor of arrhythmic events ( P  = .03). Kaplan‐Meier survival analysis revealed that ICD therapies were significantly more frequent among patients with fQRS on both surface ECG and ICD‐EGM than among those without fQRS (66.7% vs 6.6%, P  < .001). Conclusion: The presence of fQRS on ICD‐EGM can be a predictor of arrhythmic events in ICD patients. Surface ECG and ICD‐EGM measurement may help predict ventricular arrhythmic events. Abstract : We enrolled patients with implantable cardioverter defibrillator (ICD) and structural heart disease and evaluated the surface electrocardiogram (ECG) and intracardiac electrogram (EGM) measurement of fQRS and the association between fQRS and arrhythmic events.Appropriate ICD therapies were significantly higher in patients with fQRS on both surface ECG and ICD EGM than in those without.Surface ECG and ICD‐EGM measurement may help predict ventricular arrhythmic events.